Good Wives? : Mary, Fanny, Jennie & Me, 1845-2001 - Forster, Margaret (London Chatto & Windus, 2001)
Personal experiences of Margaret Forster and of her mother and grandmother, the stories of three wives who have fascinated her.
Include Illustrations, Index, Notes and Bibliography.
Mary, Fanny, Jennie & Me, 1845-2001.
Keywords: Forster, Margaret, 1938-2016 -- Lee, Jennie, 1904- -- Marriage -- Married women